The prophet - Stevens, Amanda (Don Mills, Ont. : MIRA Books, 2012)
My name is Amelia Gray. I am the Graveyard Queen, a cemetery restorer who sees ghosts. My father passed down four rules to keep me safe and I've broken every last one. A door has opened and evil wants me back. In order to protect myself, I've vowed to return to those rules. But the ghost of a murdered cop needs my help to find his killer. The clues lead me to the dark side of Charleston where witchcraft, root doctors and black magic still flourish and back to John Devlin, a haunted police detective I should only love from afar. Now I'm faced with a terrible choice: follow the rules or follow my heart.
Keywords: Murder -- South Carolina -- Charleston -- Fiction; Cemeteries -- South Carolina -- Charleston -- Fiction; Ghost stories; Paranormal romance stories; Love stories